RELATIONSHIP BETWEEN ECONOMIC AND ORGANIZED CRIME IN MODERN SOCIETY - Marija Jakovljević (Pravo, 2024)
Organized crime and related economic crime are the focus of interest for all modern, well-organized states. Theoreticians generally agree that organized crime has closely followed the development of modern states, while economic crime has evolved with the development of the economy and business, both at national and supranational levels, alongside the expansion of information and communication technologies. Despite being viewed as two distinct types of crime, economic and organized crime are highly interdependent and interconnected. While a small number of economic crime offenses lack the characteristics of organized crime, a significant number of criminal activities exhibit organized elements within the realm of the economy and economic activities. Thus, the relationship between these two types of crime is directly proportional, wherein the development of organized crime follows the development of economic crime, and vice versa. In addition to the introduction and conclusion, the paper consists of three interconnected and interrelated parts. The first part elucidates the philosophy of organized crime. It highlights the problems of defining, the lack of a unique definition, and its multidisciplinary nature. Additionally, it presents the most significant characteristics and manifestations of organized crime in theory and practice. The second part deals with the issues of economic crime. Similarly to the first part, it discusses the process of determining and defining the concept of economic crime, presenting its basic characteristics and contemporary types. Finally, the third part of the paper examines the relationship between these two categories of crime.